NEW PERSPECTIVE IN THE LEADERSHIP VALUES BASED ON BUGIS CULTURES IN “P” RESTAURANT - Jerry Rudi Lamat; Wiyono Pontjoharyo; Noviaty Kresna Darmasetiawan (Perpustakaan Universitas Surabaya, 2021)
Abstract Purpose This study aims to explore the Bugis leadership values in the small business “P” restaurant. The factors under study that are the Bugis values, SMEs, and the leadership values. Design / methodology / approach Semi-structured interviews and observations are used to collect the research data. “P” restaurant owner asked to explain the culture in the restaurant when the owner led the restaurant. Employees are asked to assess their leaders regarding perceptions about the characteristics of their leaders. Findings The results showed that the theory of cultural leadership can be applied in Indonesia. In this case the culture of leadership can be associated with leadership values Originality This research applies the value of Bugis culture in